A polêmica científica em torno da liberação do milho transgênico no Brasil - Cinaqui Filho, Edson (2015)
Transgenic organisms have inserted into its genome one or more DNA sequences of a species of interest, to ensure the inserted genic expression. Of these genes. These sequences (genes) may come from any living organismo (bactéria, fungus, plants, animals, protozoan) or nonliving (vírus). The permission for planting and commercialization of these organisms which are modified to resist various environmental pressusres raised the debate about its biosafety to the environment and to human and animal health. In this research were analyzed and discussed the decision-making processes involved in the approval of three varieties of transgenic corn in Brazil: the Liberty Link herbicide tolerant, insect resistant MON810 and Bt11 also resistant to insects. The choice of analyzing corn soybeans, is due the fact that Brazil is one of the centers of diversity of this plant and also for its importance to indigenous tribes and traditional communities. The studies submitted by the companies planning release the transgenic seeds were inadequate perfomed at short notice and grounded in statistical methods poorly documented. The samples were not representative and the number of repetitions insuficiente. Studies on the possible effects of there transgenic varieties on populations of non-target organisms were performed improperly, disregarding its ecological importante. The releases of these three varieties of transgenic com in Brazil contradicted Article 225 of the Federal Constitution which states that everyone has the right to a balanced environment which is essential to a healthy quality of life, and the Government should protect and preserve it for presente and future generations.The permission for planting and sala of transgenics occurred throught a comission in which the majority of members were interested in a transgenic research funded by multinationals. In addition to the political nature of problems, the release of transgenic corn wounded three basic environmental principles: precaution, sustainability and responsibility, for damage. Currently several studies attest problems in human and animal health and in the environment arising from transgenic organisms. Thus, the adoption of the Precautionary Principle should be essential before the release of transgenic corn in Brazil, to ensure that with so many scientific uncertainties the environment small farmers and the health human beings and other animals would be sabe. , to ensure that with so many scientific uncertainties, the environment, small farmers and the health of human beings and other animals would be safe